Principles for agrifood research and innovation: step-by-step guidance - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2022)
Investment in research and innovation today will shape the agrifood systems of the future. The choices that you make during an innovation process will affect the future benefits and drawbacks of the innovations you help to create: for example, what types of people gain and lose, and what the effects are on the environment. Too often, these choices are not made consciously, and important issues are overlooked until it is too late. The Principles will help you deliver better overall outcomes, by actively considering sustainable agrifood system objectives at key stages of your innovation projects.